Association Between Changes in Physical Activity and New-Onset Atrial Fibrillation After ICD/CRT-D Implantation - Sun, Xuerong; Zhao, Shuang; Chen, Keping; Hua, Wei; Su, Yangang; Xu, Wei; Wang, Fang; Fan, Xiaohan; Dai, Yan; Liu, Zhimin; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2021)
Background: Changes in physical activity (PA) after implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy defibrillators (CRT-D) implantation were unknown. The association of PA changes with new-onset atrial fibrillation (AF), cardiac death and all-cause mortality was unclear in patients at high risk of sudden cardiac death. Methods: Patients receiving ICD/CRT-D implantation from SUMMIT registry were retrospectively analyzed. Changes in PA were considered from baseline status to 1 year after implantation. New-onset AF was defined as the first atrial high-rate episode ≥1% of the daily AF burden detected after implantation. Results: Over a mean follow-up of 50.3 months, 124 new-onset AF events (36.2%), 61 cardiac deaths (17.8%), and 87 all-cause deaths (25.4%) were observed in 343 patients with ICD/CRT-D implantation. PA at 1 year after implantation was increased compared with PA at baseline (11.97 ± 5.83% vs. 10.82 ± 5.43%, P = 0.008), and PA at 1 year was improved in 210 patients (61.2%). Per 1% decrease in PA was associated with 12.4, 18.3, and 14.3% higher risks of new-onset AF, cardiac death and all-cause mortality, regardless of different baseline characteristics. Patients with decreased PA had 2-fold risks of new-onset AF (hazard ratio [HR] = 1.972, 95% confidence interval [CI]: 1.352–2.877, P < 0.001) as high as those with unchanged/increased PA. Decreased PA was an independent risk factor for cardiac death (HR = 3.358, 95% CI: 1.880–5.996, P < 0.001) and all-cause mortality (HR = 2.803, 95% CI:1.732–4.535, P < 0.001). Conclusion: PA decrease after ICD/CRT-D implantation is associated with a higher incidence of new-onset AF, resulting in worsened outcomes in cardiac death and all-cause mortality.